Biomimicry : innovation inspired by nature - Benyus, Janine M. (William Morrow, 2002)
Biomimicry is a revolutionary new science that analyzes nature's best ideas--spider silk and eyes, seashells and brain cells, photosynthesis and DNA--and adapts them for human use. Janine Benyus takes us into the lab and out in the field with the maverick researchers who are discovering nature's ingenious solutions to the problem of human survival: studying leaves to learn how to make microscopic solar power packs that will clean up toxic spills and light our homes; harnessing DNA's coding power to make blindingly fast computers; discovering miracle drugs by observing what animals eat; and much more. The answers are there for the finding, poemlike in their elegance and economy. Anyone interested in the people and ideas that are shaping our future must read this book to know where the most exciting revelations lie literally all around us.